An erosion and sediment delivery model for semi-arid catchments - Bryson, Louise Kay (Rhodes University, Faculty of Science, Institute for Water Research, 2016)
Sedimentation has become a significant environmental threat in South Africa as it intensifies water management problems in the water-scarce semi-arid regions of the country. As South Africa already allocates 98% of available water, the loss of storage capacity in reservoirs and degraded water quality has meant that a reliable water supply is compromised. The overall aim of this thesis was to develop a catchment scale model that represents the sediment dynamics of semi-arid regions of South Africa as a simple and practically applicable tool for water resource managers. Development of a conceptual framework for the model relied on an understanding of both the sediment dynamics of South African catchments and applicable modelling techniques. Scale was an issue in both cases as most of our understanding of the physical processes of runoff generation and sediment transport has been derived from plot scale studies. By identifying defining properties of semi-arid catchments it was possible to consider how temporal and spatial properties at higher levels emerged from properties at lower levels. These properties were effectively represented by using the Pitman rainfall-runoff model disaggregated to a daily timescale, the Modified Universal Soil Loss Equation (MUSLE) model incorporating probability function theory and through the representation of sediment storages across a semi-distributed catchment. The model was tested on two small and one large study catchment in the Karoo, South Africa, with limited observed data. Limitations to the model were found to be the large parameter data set and the dominance of structural constraints with an increase in catchment size. The next steps in model development will require a reduction of the parameter data set and an inclusion of an in-stream component for sub-catchments at a larger spatial scale. The model is applicable in areas such as South Africa where water resource managers need a simple model at the catchment scale in order to make decisions. This type of model provides a simple representation of the stochastic nature of erosion and sediment delivery over large spatial and temporal scales.
Keywords: Sedimentation and deposition; Erosion; Watershed management -- South Africa; Water-supply -- South Africa